1997
DOI: 10.1016/s0020-0255(96)00152-1
|View full text |Cite
|
Sign up to set email alerts
|

Alternative distributed models for the comparative study of stock market phenomena

Abstract: In this paper we present a methodology of study of complex phenomena emerging in stock markets. This methodology is based on the use of distributed, multi-agent models with minimal knowledge representation and reasoning capabilities that has proven a powerful modeling tool for complex biological systems. Unlike neural and "neo-connectionist" models, ours' allow a comparative and incremental evaluation of their validity and relevance to the observed phenomena. The possibility of their application to the modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Regarding financial decisions overconfidence was analytically (e.g., Barber and Odean 1999, Benos 1998, Caballé and Sákovics 2000 and experimentally (e.g., Adams et al 1995, Benos and Tzafestas 1997, Camerer and Lovallo 1999 studied and also confirmed for field data (e.g., Odean 2000, Statman andThorley 1999). Overconfident investors trade too much (Biais et al 2000, Odean 1998, deviate from Bayes' rule when aggregating information (Nöth and Weber 2000), and overreact to private and underreact to public signals (Daniel et al 1998).…”
Section: Introductionmentioning
confidence: 78%
“…Regarding financial decisions overconfidence was analytically (e.g., Barber and Odean 1999, Benos 1998, Caballé and Sákovics 2000 and experimentally (e.g., Adams et al 1995, Benos and Tzafestas 1997, Camerer and Lovallo 1999 studied and also confirmed for field data (e.g., Odean 2000, Statman andThorley 1999). Overconfident investors trade too much (Biais et al 2000, Odean 1998, deviate from Bayes' rule when aggregating information (Nöth and Weber 2000), and overreact to private and underreact to public signals (Daniel et al 1998).…”
Section: Introductionmentioning
confidence: 78%
“…Regarding financial decisions overconfidence was analytically (e.g., Barber and Odean 1999, Benos 1998, Caballé and Sákovics 2000 and experimentally (e.g., Adams et al 1995, Benos and Tzafestas 1997, Camerer and Lovallo 1999 studied and also confirmed for field data (e.g., Odean 2000, Statman andThorley 1999). Overconfident investors trade too much (Biais et al 2000, Odean 1998, deviate from Bayes' rule when aggregating information (Nöth and Weber 2000), and overreact to private and underreact to public signals (Daniel et al 1998).…”
Section: Introductionmentioning
confidence: 78%
“…Experimental studies also have demonstrated that people tend to underestimate their error variance in making predictions, and overweight their own forecasts relative to those of other forecasters (e.g., Lichtenstein et al, 1982;Yates, 1990;Batchelor and Dua, 1992;Benos and Tzafestas, 1997). To empirically evaluate the above hypothesis, we need to identify private and public information.…”
Section: Empirical Frameworkmentioning
confidence: 99%